Pengaruh Earning Per Share (EPS), Price To Earning Ratio (PER), Dan Price To Book Value (PBV) terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bei Periode 2018-2022 - Reka Widiana; Yoyok Prasetyo; Nani Ernawati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This study aims to analyze the effect of Earning Per Share (EPS), Price to Earning Ratio (PER), and Price to Book Value (PBV) on the share price of banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022. The approach used in this research is quantitative and associative approach. the population used is 47 banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. With the sampling technique using purposive sampling technique as many as 28 banking companies. The results showed that the variables Earning Per Share (EPS), Price to Earning Ratio (PER), and Price to Book Value (PBV) simultaneously influenced the share price of banking companies listed on the IDX for the 2018-2022 period.